INDONESIAN EFL PRE SERVICE TEACHER’S PERCEPTIONS AND ACCEPTANCE OF THE USE OF TECHNOLOGY DURING A TEACHING PRACTICE - Muhammad Khoerul Hadist (STKIP Muhammadiyah Bogor, 2020)
This research was conducted to find out the Indonesian EFL pre-service teachers’ perception and acceptance in using technology during a teaching practice. The research was used mix method research approach. The questionnaire and interview used as the instrument of research to the sixty Indonesian EFL pre service teachers. The research discovered that Indonesian EFL pre service teachers have positive perception and positive acceptance in using technology during teaching practice.